2019
DOI: 10.1055/s-0039-1695050
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Disease in Women

Abstract: There are several pleural diseases that occur either predominantly or exclusively in females. Most of these entities are related to obstetric or gynecological conditions. In this article, we will provide an overview of Meigs' syndrome, ovarian hyperstimulation syndrome, endometriosis, catamenial pneumothorax, catamenial hemothorax, pleural effusions that occur in the peripartum period, lymphangioleiomyomatosis, and malignant pleural effusions related to breast cancer. As most of these diagnoses are rare, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…18-21%) [3][4][5]. Unlike previous studies, we performed noninvasive chest ultrasonography on all patients with severe OHSS and found that 52% of the patients had hydrothorax (bilateral: >60%; mild to moderate: 93%, massive: 7%).…”
Section: Ohss and Hydrothoraxmentioning
confidence: 79%
See 1 more Smart Citation
“…18-21%) [3][4][5]. Unlike previous studies, we performed noninvasive chest ultrasonography on all patients with severe OHSS and found that 52% of the patients had hydrothorax (bilateral: >60%; mild to moderate: 93%, massive: 7%).…”
Section: Ohss and Hydrothoraxmentioning
confidence: 79%
“…Hydrothorax is one manifestation of severe and critical OHSS [2], with an incidence of 23-29%. Hydrothorax is more common on the right side due to the anatomy of the right diaphragm [3][4][5]. For patients with severe OHSS, does the presence of hydrothorax suggest more severe conditions or worse pregnancy outcomes?…”
Section: Introductionmentioning
confidence: 99%
“…It represents 2-5% of surgically removed ovarian tumors. Meigs syndrome is most common in postmenopausal women [ 1 ], and its incidence peaks in the seventh decade [ 3 ]. It can also be seen in children [ 1 ] in whom the annual incidence of ovarian masses is only 2.6 cases/100,000 girls [ 5 ], making ovarian masses a rare occurrence during childhood and Meigs syndrome even rarer [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meigs syndrome is a rare disorder [ 1 ] comprising a triad of benign ovarian tumor, ascites, and pleural effusion. Despite its benign nature, its presentation mimics a metastatic malignancy [ 2 ], rendering preoperative diagnosis often challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation